Associação entre os polimorfismos de MCP-1 rs1024611 e de IL-17 rs2275913 com a hanseníase - Fonseca, Adriana Barbosa de Lima (2016)
Leprosy is a chronic infection caused by Mycobacterium leprae which affects skin and peripheral nerves. Various aspects related to genetic and phenotypic variability of the pathogenesis of immune response need to be further studied. In leprosy several polymorphisms of genes involved in the immune response of the host to pathogen were associated with leprosy per se and its clinical course. This present case-control study aimed to examine the possible association between polymorphisms rs2275913 of IL-17 and rs1024611 of MCP-1 with leprosy. The sample was composed of 199 patients and 85 healthy individuals unrelated households of the cases. The polymorphisms were analyzed using the PCR technique Taqman. For statistical analysis we used the software SPSS version 22.0 with employment of the Student T test for independent samples, Chi-square and Fisher's exact test where appropriate and analysis thereof. There were differences in the distribution of genotypes of MCP-1 and IL-17 between leprosy and contactant controls (p = 0.015 and p = 0.031 respectively) with greater frequency of genotype GG in the leprosy patients. The comparison of the distribution of genotypes between the groups stratified by multibacillary and paucibacillary clinical forms, did not show any difference in the distribution of genotypes of either MCP-1 or IL-17 in the patients with the operacional forms (p = 0.46 and p=0.14 respectively). The analysis of sick and healthy individuals according to the variables age, sex and genotypes of MCP-1 and IL-17 allowed to discriminate five groups. Groups 1 and 5 were composed of patients who had only the GG genotype of IL-17 while the GG genotype of MCP-1 was more frequent in Group 1 which was composed of mostly patients (p = 0.0001). Possibly the presence of genotype GG of MCP-1 and IL-17 GG genotype contributed to the outcome of the disease in the studied subjects.